Pola Dominansi Capit pada Uca spp. (Dekapoda:Ocypodidae) - Dewi Citra Murniati (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2010)
Uca spp. are unique crab species marked with asymmetry cheliped. Major and minor cheliped has different function. The size of Major cheliped are several times of the minor ones (cheliped dominance pattern). Each species has different pattern of cheliped dominance. This study was to know the pattern of cheliped dominance on three Uca species. Major and minor cheliped length from twenty male individuals of U. dussumieri, U. vocans and U. perplexa were examined. The pattern of Cheliped dominance was obtained by comparing the major cheliped length to minor cheliped length. The two-tailed single sample t test showed similar cheliped dominance pattern within Uca species (P>0.001). While Kruskal-Wallis test showed different cheliped dominance pattern between Uca species (P>0.001). The cheliped dominance pattern of U. dussumieri, U. vocans and U. perplexa are 5.09, 4.24 and 4.75.